NECTIN-4-redirected T cell Antigen Coupler T cells bearing CD28 show superior antitumor responses against solid tumors - Wei, Cheng; Huang, Xin; Xu, Tianlong; Fang, Yinan; Wang, Fabao; He, Qiaolin; Zhang, Peiyuan; Yu, Qianjin; Zhang, Ying; Zheng, Binjiao; Gao, Yue; Chen, Yongping; et al. (Frontiers in Immunology, 2024)
IntroductionT cell Antigen Coupler (TAC) T cells harness all signaling subunits of endogenous T cell receptor (TCR) to trigger T-cell activation and tumor cell lysis, with minimal release of cytokines. Some of the major obstacles to cellular immunotherapy in solid tumors include inefficient cell infiltration into tumors, lack of prolonged cellular persistence, and therapy-associated toxicity.MethodsTo boost the cytotoxic potential of TAC-T cells against solid tumors, we generated a novel NECTIN-4-targeted TAC-T variant, NECTIN-4 TAC28-T, which integrated the co-stimulatory CD28 cytoplasmic region, and compared the anti-tumor activities between NECTIN-4 TAC-T cells and NECTIN-4 TAC28-T cells in vitro and vivo.ResultsWe demonstrated NECTIN-4 TAC28-Tcells could be effectively activated by NECTIN-4 protein-coated magnetic beads (NECTIN-4-beads), and further revealed that the incorporated CD28 co-stimulatory domain enhanced their activation and proliferation capabilities. Notably, NECTIN-4 TAC28-T cells exhibited better anti-tumor effects both in vitro and in vivo than the original NECTIN-4 TAC-T cells.DiscussionOur data highlighted that NECTIN-4 TAC28-T cells may represent a promising, safe and effective cell therapy for NECTIN-4-overexpressing solid tumors.